(untitled) (African Journal of Science, Technology and Social Sciences, 2025)
Particulate matter (PM) pollution poses a significant threat to public health in urban environments worldwide. Rapid urbanization, coupled with industrial activities and inadequate environmental regulations, often exacerbate this challenge. This study investigates the extent of PM pollution in three Kenyan cities - Nairobi, Kisumu, and Meru Town - to assess their air quality and potential health risks for residents. Leveraging the high temporal resolution of Internet of Things (IoT)-enabled Optical Particle Counters (OPCs), the research collected real-time PM data across various locations within each city. Data analysis, encompassing historical information dating back to 2020, revealed consistently elevated PM levels across all study sites, exceeding the World Health Organization’s (WHO) recommended air quality thresholds. These findings highlight the critical need for comprehensive air quality monitoring programs across urban centers in Kenya. By quantifying the severity of PM pollution, this research underscores the urgency for policymakers to address this public health threat. The study emphasizes the importance of implementing stricter environmental regulations and developing targeted strategies to mitigate PM emissions, ultimately promoting cleaner air and safeguarding the health of residents in Kenyan cities.